SOME CONSIDERATIONS IN ORAL TEST - Emilia Ninik Aydawati (Celt: A Journal of Culture, English Language Teaching & Literature, 2003)
Most English teachers usually conduct oral tests based on their intuition. They do not use any theoretical basis in scoring. In some English courses, even though there is a routine meeting to discuss material, method and other things, which relate to learning teaching activities, they do not pay much attention in discllssing scoring system. So far teachers give score on learners 'oral proficiency or achievement based on the notes they may make during the interview or just based on their general impression without tryillg to analyse some dW'erent aspects of the learners' speaking ability. Perhaps they neglect to make a scoring guide because it is 1I0t easy alld it takes time. Oral test can often be more difficult to design, administer and mark. It is sometimes felt that giving someone all oral interview is a quick and painless way of assessing that persoll:~ oral proficiency. Actually a speaking test is a repeatable procedure to measure speaking ability that requires the learner to speak, or to produce utterances and he/she is assessed 011 the basis of his/ her utterances. III order to measure his/her speaking ability, teachers may use some speaking prompts, such as picture, topic or photograph but they do 1I0t use any scoring guide in their marking process. Since Oral test has got only less attention than other skills, this paper is directed to show some considerations in oral test: steps in developing oral test, type of oral test and its marking system, including validity alld reliability.